1997
DOI: 10.1002/zaac.19976230124
|View full text |Cite
|
Sign up to set email alerts
|

Di(fluorosulfato)‐di(acetonitril)dimethylzinn(IV) [Me2Sn(OSO2F)2(NCMe)2]: Bildung und molekülstruktur

Abstract: Inhaltsiibersicht. Ein Einkristall des Titelkomplexes (4) ent-phischer Inversionssymmetrie (Sn-C 209,2, Sn-0 225,8, stand zufallig bei Versuchen, rontgentaugliche Kristalle der Sn-N 235,9 pm, &-Winkel 87-93'). Die als einzahniger bekannten Verbindung Me2Sn[N(S02F)2]2 (3) aus Acetoni-0-Ligand wirkende FS03-Gruppe weicht nicht stark von C3vtril zu zuchten. Die thermolabile Substanz 4 kann gezielt aus Symmetrie ab (Mittelwerte: S-0 143,4, S-F 156,8pm, 0-S-0 114,9, Me2Sn(OS02F)2 und MeCN dargestellt werden. Die Kr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
0

Year Published

1997
1997
2015
2015

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 19 publications
2
10
0
Order By: Relevance
“…The planar angles of the SnO 4 core group sum to 360 ± 0.1° in these compounds. The O−S−O angles of the methanesulfonate groups are similar to those found in other related organotin derivatives. …”
Section: Resultssupporting
confidence: 72%
See 2 more Smart Citations
“…The planar angles of the SnO 4 core group sum to 360 ± 0.1° in these compounds. The O−S−O angles of the methanesulfonate groups are similar to those found in other related organotin derivatives. …”
Section: Resultssupporting
confidence: 72%
“…However, these are comparable to the corresponding Sn−O bond distances reported for hydroxodi- n -butyltin perchlorate [2.425(5) Å] 11 and hydroxodimethyltin nitrate [2.30(3) Å], reflecting appreciable ionic character for these bonds. Sn−C and S−O bond distances are normal. The presence of the S−C bond [1.721(7) Å for 6 ; 1.744(13), 1.742(11) Å for 10 ] conclusively proves the identity of methanesulfonate group in these compounds. The Sn···Sn bond distances (4.816−4.986 Å) are much longer than some of the van der Waals radii .…”
Section: Resultsmentioning
confidence: 85%
See 1 more Smart Citation
“…Indeed, the C 1 conformer is found in crystals of M + FSI -(M + ) Li + , K + , C 6 H 6 ‚Ag + ), [4][5][6] whereas the C 2 conformer is found in crystals of M + FSI -(M + ) Cs + , CHCl 3 ‚ Ph 3 C + , Ph 3 PH + , and (CH 3 ) 3 Pb + and a series of Xe(II) derivatives). [7][8][9][10][11][12] This evidently indicates that the conformation strongly depends on an ionic environment around the FSIion. Furthermore, the sole C 1 conformer of TFSIis involved in EMI + TFSIcrystals, 13 whereas both C 1 and C 2 conformers are present in the liquid and glassy states.…”
Section: Introductionmentioning
confidence: 91%
“…33 Tin triflates 34 are much less studied than silicon tri- flates but have been used as Lewis-acid catalysts in a handful of organic transformations. 35 There are a number of structurally characterised tin triflates, 12,[36][37][38][39][40][41][42][43] and examples of fourcoordinate tin triflates include [Sn{CH(SiMe 3 ) 2 } 3 OTf ] synthesised by protonation of the corresponding tin hydride using HOTf 44 and another from protonation of a strained [2]ferrocenophane with a CH 2 Sn( t Bu) 2 bridge forming a fourcoordinate tin triflate. 45 Reactions of AgOTf with 12-15 were carried out generating the corresponding tin triflates 16, 17 and 19 but 1 H NMR spectroscopy revealed that reactions to generate 18 also generated other unidentified by-products which could not be separated.…”
Section: Formation Of Tin Triflatesmentioning
confidence: 99%